Evaluation of Sous-Vide Technology in Gastronomy - Yıkmış, Seydi; Aksu, Harun; Çöl, Başak Gökçe; Demirçakmak, İbrahim Levent (Skyfox Publishing Group, 2018)
Sous vide is cooked under control by applying a certain temperature (65-96 oC) / time after vacuuming in the package of the food which is formed alone or with other auxiliary products (sauce-spices) and stored under cold conditions (1-4 oC) by rapidly reducing the temperature after heat application This process is also known as lapping, vacuum cooking, vacuum packed cooking with vacuum pack or baking-cooling with vacuum packaged. In the products prepared by this technology, the blocking effect provided by oxidative and aerobic bacteria development through vacuum packaging combines with microbial protection effect provided by pasteurization; Thanks to the applied cold chain, a long and safe shelf life is provided and consumed. Food can be made reliable by pasteurizing at low temperatures, and even safely consumed without cracking and crunchy foods. In addition to all these advantages, sous vide technology also has some disadvantages. When the investigations are examined, it has been concluded that the research on sous vide technology's reliability in terms of health should be intensified.
Keywords: Research Subject Categories::TECHNOLOGY